Annual Plan 2000-01 - Planning Commission (Planning Commission, 2000)
The Ninth Five Year Plan (1997-2002) has been formulated in the context of three important dimensions of state policy and against a perspective of development for fifteen years. Quality of life, generation of productive employment and regional balance summarise the main dimensions of its state policy. The Plan focussed on accelerated growth recognising a special role for agriculture for its stronger poverty reducing and employment generating effects, which will be earned out over a fifteen year period of framework of consistent policies. It recognised the need for well designed set of policies for ensuring food and nutritional security.
Government of India Planning Commission
Government of India Planning Commission